Factors Affecting Parental Satisfaction with Ponseti Treatment in Children with Clubfoot: Parental Satisfaction with Ponseti Treatment in Children with Clubfoot - Ali, Pervez; Mengal, Muhammad Aslam; Soomro, Shazia; Bux, Wahid; Ghaffar, Abdul; Khan, Sharjeel; Ahmed, Mehtab (Pakistan Journal of Health Sciences, 2025)
Clubfoot, also known as congenital talipes equinovarus (CTEV), is a common lower-limb developmental disorder. Objectives: To assess the factors affecting parental satisfaction with Ponseti treatment in children with clubfoot presenting at a tertiary care hospital. Methods: It was a cross-sectional study carried out in the Department of Orthopaedics, Jinnah Postgraduate Medical Centre (JPMC), Karachi, Pakistan, from January 2024 to December 2024. We enrolled the 150 parents (either mother or father of children aged more than 18 years) of children diagnosed with clubfoot and who were undergoing Ponseti treatment. Parents were interviewed, and data were collected on socio-demographic factors, and their satisfaction level was assessed using a modified orthotics prosthetics user survey. Data were analysed using SPSS version 23. Results: The median age of the parents was 39 years, and most were female (54%). 59.3% of the parents were satisfied with the Ponseti clubfoot treatment, and 40.7% were unsatisfied. The multivariate analysis revealed female gender (AOR=17.90, 95% CI=6.05-53.29), duration of treatment ≥8 months (AOR=8.30, 95% CI: 2.88-23.93), being employed (AOR=8.76, 95% CI=2.65-29), primary education (AOR=5.69, 1.49-21.62), intermediate education (AOR=7.35, 1.84-29.35) and graduate level education (AOR=10.80, 95% CI=2.52-46.19) were identified as major factors for parental satisfaction for ponseti treatment in children with clubfoot. Conclusions: It was concluded that factors such as being a father, children with short duration of treatment, having no job and education are significantly associated with parental dissatisfaction. Therefore, appropriate educational interventions should be devised to improve treatment results and adherence rates.